Respuesta :

Answer      

:x=5 y=6

Step-by-step explanation:

Answer:

x=5 y=6

Step-by-step explanation:

Need to get rid of one variable to find one first. So I multiplied the second equation by -2 to get rid of y. So second equation becomes 12x-6y=24. add that to the first equation.

6x+6y=6

12x-6y=24

6x=30      then divide

x=5

then plug x into the original equation to get y.

-6(5) +6y=6

-30+6y=6    add 30 to both sides

6y=36       then divide

y=6

then put both into the original to make sure it makes sense

-6(5) +6(6)=6

-30+36=6

6=6

correct